The influence of sulforaphane on vascular health and its relevance to nutritional approaches to prevent cardiovascular disease - Evans, Paul C. (Springer Netherlands, 2011)
Oxidation of low-density lipoproteins (LDL) promotes atherosclerosis by enhancing vascular inflammation and foam cell formation. The corollary is that diets that stimulate endogenous anti-oxidants may protect against atherosclerosis. This review focuses on sulforaphane, an isothiocyanate derived from green vegetables, which induces multiple anti-oxidant enzymes via activation of a transcription factor called Nrf2. Although studies of cultured cells and experimental animals revealed that sulforaphane can suppress inflammatory activation of vascular cells, the potential beneficial effects of sulforaphane in atherosclerosis have not been studied directly. A deeper understanding of vascular responses to sulforaphane may inform nutritional approaches to prevent vascular inflammation and atherosclerosis.